Eruption times and patterns of permanent teeth in school children of India - Ambika Lakshmappa; Mahima Veeranna Guledgud; Karthikeya Patil (Wolters Kluwer Medknow Publications, 2011)
Aim: To study the eruption pattern of permanent teeth excluding third molars in school children of Mysore, South India. Objectives: To compare the eruption times determined with previous studies. To determine range of variation of the eruption time of each tooth and evaluate if any preponderance exists in the eruption timings of maxillary and mandibular teeth and between boys and girls. Materials and Methods: This was a descriptive cross sectional study. A random sample of 5007 school children in the age group of 5-14 years was selected. The mean age of eruption of individual permanent teeth was recorded and results were analyzed using Probit analysis. Results: The study population included 2371 boys constituting 47.26% and 2636 girls constituting 52.65% of the total sample. In the age group of 5 years, one of the permanent teeth was found to be erupted. In the age group of 14 years, all the permanent teeth except third molar had erupted. Girls showed early tooth eruption compared to boys. Mandibular teeth erupted earlier than maxillary teeth in both the sexes. Right and left sided teeth erupted at the same time in both the arches. Conclusion: The mean ages of eruption obtained from the present study are strikingly comparable with those of other investigators in different populations across the world. Since the current study involves a large sample of children, the data reported in this study could be used as standards when assessing permanent tooth eruption in Indian children.